Improving Student Competence MYOB Accounting, Data Processing, and Financial Literacy at Tanjung Pinang SMK Negeri 1 - Dian Efriyenti; Hikmah Hikmah; Khadijah Khadijah (EQUATOR SINAR AKADEMIA, 2023)
The ability of students of SMK Negeri 1 Tanjung Pinang Accounting Department in the field of data processing is still very low, so it is necessary to provide training in the form of application practise using MYOB computers so as to gain expertise at the national level. The sustainability of the results of this activity is that vocational students are able to input and output financial results with the help of MYOB software. The continuation of this activity is to record finances to record financial reports. Students of SMK Negeri 1 can prepare standard financial reports for small and medium micro-financial entities in accordance with the financial reporting cycle. Students understand the accounting cycle and the preparation of financial reports according to entity financial accounting standards without public accountability. Students of SMK Negeri 1 understand the use of MYOB accounting practices from physical evidence to producing financial reports. And students are aware of the importance of using banking services and products and choosing strategies and taking risks.